The relationship of parenting with juvenile delinquency review of David Ozora’s abuse case study by Mario dandy - Sri Wahyuni Wahyuni; Amanda Yulianti; Fitriana Abdullah; Cecep Abdul Mu'ti; Tri Budi Jatmiko (Institute of Computer Science (IOCS), 2023)
The media intensively reported on the juvenile delinquency committed by Mario Dandi, resulting in the permanent disability of David Ozora. As many responses have come from several practitioners and experts, these cruel acts are the impact of improper parenting.This study aims to theoretically analyze the parenting style applied by Mario Dandy's parents, as described by experts. Research is designed using literature studies, with data analysis using descriptive methods. The results revealed that the parenting style applied by Mario Dandy's parents tends toward permissive and authoritarian parenting styles. This was analyzed by looking at Mario Dandy's behavior when committing violent acts as well as the actions of his parents while the legal process was on going.